Lower cognitive function in patients with age-related macular degeneration: a meta-analysis - Zhou LX (Dove Medical Press, 2016)
Li-Xiao Zhou,1 Cheng-Lin Sun,1 Li-Juan Wei,1 Zhi-Min Gu,1 Liang Lv,1 Yalong Dang21Department of Ophthalmology, The Fifth Affiliated Hospital of Zhengzhou University, 2Department of Ophthalmology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of ChinaObjective: To investigate the cognitive impairment in patients with age-related macular degeneration (AMD).Methods: Relevant articles were identified through a search of the following electronic databases through October 2015, without language restriction: 1) PubMed; 2) the Cochrane Library; 3) EMBASE; 4) ScienceDirect. Meta-analysis was conducted using STATA 12.0 software. Standardized mean differences with corresponding 95% confidence intervals were calculated. All of the included studies met the following four criteria: 1) the study design was a case–control or randomized controlled trial (RCT) study; 2) the study investigated cognitive function in the patient with AMD; 3) the diagnoses of AMD must be provided; 4) there were sufficient scores data to extract for evaluating cognitive function between cases and controls. The Newcastle–Ottawa Scale criteria were used to assess the methodological quality of the studies.Results: Of the initial 278 literatures, only six case–control and one RCT studies met all of the inclusion criteria. A total of 794 AMD patients and 1,227 controls were included in this study. Five studies were performed with mini-mental state examination (MMSE), two studies with animal fluency, two studies with trail making test (TMT)-A and -B, one study with Mini-Cog. Results of the meta-analysis revealed lower cognitive function test scores in patients with AMD, especially with MMSE and Mini-Cog test (P≤0.001 for all). The results also showed that differences in the TMT-A (except AMD [total] vs controls) and TMT-B test had no statistical significance (P>0.01). The Newcastle–Ottawa Scale score was ≥5 for all of the included studies. Based on the sensitivity analysis, no single study influenced the overall pooled estimates.Conclusion: This meta-analysis suggests lower cognitive function test scores in patients with AMD, especially with MMSE and Mini-Cog test. The other cognitive impairment screening tests, such as animal fluency test and TMT, need more studies to assess.Keywords: age-related macular degeneration; cognitive impairment; meta-analysis; mini mental state examination